Understanding Absorption Laws (Boolean Algebras)

  • I
  • Thread starter mathrookie
  • Start date
  • Tags
    Logic
In summary: Thanks.In summary, the absorption law is obtained by using the distributive law in Boolean Algebras. This allows for the expression to be simplified to ##a∧(a∨b)## and ultimately to ##a##. Some people may refer to it as distribution law, but it is the same concept.
  • #1
mathrookie
1
0
TL;DR Summary
I cannot apply distribution law
I can't understand how absorption law is obtained. I get following steps.##a∨(a∧𝑏) = (a∧⊤)∨(a∧𝑏)##
##=(a∨a)∧(a∨b)∧(⊤∨a)∧(⊤∨b)##
then,

I come up with ##=a∧(a∨b)∧⊤∧⊤## so ##=a∧(a∨b)##

But, I cannot get ##a∧(⊤∨𝑏)##, as shown on here, therefore ##a##.

Can you help me? I cannot obtain ##a∧(⊤∨𝑏)## Some people say in other answers in different questions, it is obtained by distribution law. However, what I got by this is the first equation.
[1]: https://proofwiki.org/wiki/Absorption_Laws_(Boolean_Algebras)
 
Physics news on Phys.org
  • #2
mathrookie said:
TL;DR Summary: I cannot apply distribution law

I can't understand how absorption law is obtained. I get following steps.##a∨(a∧𝑏) = (a∧⊤)∨(a∧𝑏)##
##=(a∨a)∧(a∨b)∧(⊤∨a)∧(⊤∨b)##
Your expression above doesn't help.
Follow the logic in your link to get this:
##a ∨ (a∧𝑏) = (a∧⊤)∨(a∧𝑏)##
##= a ∧ (T ∨ b) ## ∧ distributes over ∨
## = a ∧ T = a## T ∨ b = T
Edited to fix earlier typo.
mathrookie said:
then,

I come up with ##=a∧(a∨b)∧⊤∧⊤## so ##=a∧(a∨b)##

But, I cannot get
##a∧(⊤∨𝑏)##, as shown on here, therefore ##a##.

Can you help me? I cannot obtain
##a∧(⊤∨𝑏)## Some people say in other answers in different questions, it is obtained by distribution law. However, what I got by this is the first equation.
[1]: https://proofwiki.org/wiki/Absorption_Laws_(Boolean_Algebras)
 
Last edited:
  • #3
Mark44 said:
Your expression above doesn't help.
Follow the logic in your link to get this:
##a ∨ (a∧𝑏) = (a∧⊤)∨(a∧𝑏)##
##= a ∧ (T ∧ b) ## ∧ distributes over ∨
## = a ∧ T = a## T ∨ b = T
Slight typo here, should be ##a\wedge(\top\vee b)##
OP, you can also use a truth table to see that the two expressions must be equal to a.
 
  • #4
TeethWhitener said:
Slight typo here, should be ##a\wedge(\top\vee b)##
Right. I've fixed it in my post.
 
  • Like
Likes TeethWhitener

Similar threads

  • Set Theory, Logic, Probability, Statistics
Replies
21
Views
2K
  • Set Theory, Logic, Probability, Statistics
Replies
9
Views
1K
  • Set Theory, Logic, Probability, Statistics
Replies
4
Views
2K
  • Set Theory, Logic, Probability, Statistics
Replies
7
Views
392
  • Set Theory, Logic, Probability, Statistics
Replies
5
Views
991
  • Set Theory, Logic, Probability, Statistics
Replies
6
Views
997
  • Set Theory, Logic, Probability, Statistics
Replies
18
Views
4K
  • Set Theory, Logic, Probability, Statistics
2
Replies
40
Views
6K
  • Set Theory, Logic, Probability, Statistics
Replies
10
Views
3K
  • General Math
2
Replies
47
Views
3K
Back
Top